Aktivitas Ekstrak Daun Binahong(Anredera cordifolia (Ten.) Steenis) sebagai Antihiperurisemia dan Antioksidan pada Tikus Hiperurisemia - Laksmitawati, Dian Ratih; Simbolon, Roslan (Indonesian Research Gateway)
ABSTRACT : The Binahong plant (Anredera cordifolia (Ten.) Steenis) has been used to treat several types of diseases. To find another possible biological activities, we investigated binahong leaves antihyperuricemic and antioxidant activity through in vitro assay of xanthine oxidase inhibiting activity of binahong ethanol extract and through in vivo assay by measuring uric acid and malondialdehyde (MDA) levels in plasma of hyperuricemic rat treated with binahong ethanol extract. Rat was induced into hyperuricemiccondition using chicken concentrate which is administered orally for 7 days and potassium oxonic through intraperitoneal routeon the last day. In treatment groups, rat were administered with extract at doses 200, 400 and 800 mg/kg BW respectively along the induction periods, while theother group were given allopurinol. On 7thday, the levels of plasma uric acid andMDA were measured by enzymatic methods and tiobarbituric acid reactive substances (TBARS) methodconsecutively. In vitro study shows that at 100 ppm,binahong leavesethanolic extract inhibit xanthine oxidase activity by24.33%, while in vivo study showedthe extract hadantihyperuricemic activity by decreasinguric acid levels at dose 800 mg / kgBB about 60,88% compared to hyperuricemia control group. Plasma MDA levels showed that hyperuricemia induction for 7 days was not enough to show significant increase of MDA levels.As conclusion, the ethanolic extract of binahong leaves could lower uric acid levels but in this study it’s activity as antioxidant could not be proven through MDA measurements.